2016
DOI: 10.1016/j.ijpvp.2016.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Optimized bolt tightening strategies for gasketed flanged pipe joints of different sizes

Abstract: Achieving a proper preload in the bolts of a gasketed bolted flanged pipe joint during joint assembly is considered important for its optimized performance. This paper presents results of detailed non-linear finite element analysis of an optimized bolt tightening strategy of different joint sizes for achieving proper preload close to the target stress values. Industrial guidelines are considered for applying recommended target stress values with TCM (torque control method) and SCM (stretch control method) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…where i denotes the corresponding i-th column in Table 5 (i = 1, 2, 3, 4, 5), n sp denotes the number of repetitions of level (in this article, n sp = 5), T denotes the sum of the data, and n z denotes the total number of data points (in this article, n z = 25). The degree of freedom corresponding to the sum of squared deviations of the factor can be calculated as equation (2).…”
Section: Variance Analysis Of Experimental Resultsmentioning
confidence: 99%
“…where i denotes the corresponding i-th column in Table 5 (i = 1, 2, 3, 4, 5), n sp denotes the number of repetitions of level (in this article, n sp = 5), T denotes the sum of the data, and n z denotes the total number of data points (in this article, n z = 25). The degree of freedom corresponding to the sum of squared deviations of the factor can be calculated as equation (2).…”
Section: Variance Analysis Of Experimental Resultsmentioning
confidence: 99%
“…In 2000, Schaumann and Seidel present failure analysis results from detailed nonlinear FE calculation of bolted steel ring flange connections, and bearing capacity of the structure under quasistatic load has been predicted, but the failure criterion of the structure is plastic deformation, and the fracture failure mode of the bolts is not demonstrated in the research [15]. Abid and Nash have investigated the sealing property and tightening strategies for gasket flanged with bolted joint used by a solid FEM [16,17]. In 2016, Bartlomiej and Witold established a finite element model through applying a multilevel substructuring approach and a reduction of DOFs using the static condensation method, and the mechanical behavior of the complex structure composed of tubular beams and bolted connections has been investigated [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, application of thermal loading has not been considered to date, due to its complexity of application during experimental studies. In addition, Abid et al and Fukuoka et al [4][5][6][7][8][9][10][11] in their numerical studies have concluded that gasketed joints show better sealing performance if bolts in a joint are tightened as per ASME bolt tightening strategy [12] as compared to the various accepted industrial practices [13].…”
Section: Introductionmentioning
confidence: 99%